Architectural Media and Knowledge Management for Tourism Development: A Case Study of Museum Traveling in Ayutthaya World Heritage Site - Tongaroon, Nirandorn (Journal of Architectural/Planning Research and Studies (JARS), 2018)
Ayutthaya is the most significant root of civilization for the study of architectural and history of the nation with organizations from both government and private sector in part of management, conservation, and development, that progress the learning of architectural value and tourism industry, especially in the potential area of Ayutthaya island. These include the established sources of information and historical agencies in tourism development, which includes museum, cultural center, information centers, and etc. The distribution of information is also informed in term of architectural media and data knowledge with two and three dimensions that provide for learning and education, or visiting the site. However, the quality of learning content seem to be limited in the learning process which the audience can not have an alternative to access the area of interest due to the content is determined by organizer’s format. This situation reflects to the media and data knowledge and the tourism industry development and can not be carried out by the way it should be. This research had studied on both theories and related issues, focusing on media and data knowledge development such as data collection and data media of Ayutthaya island. These studies are about transportation, accessibility, and traveling routes in order to set up the presentation guideline for physical Ayutthaya island in architectural multimedia and virtual environmental. Especially, the media will provide an option in the learning process, museum presentation, and alternative of Ayutthaya’s study image such as path, canal, river, traffic, node, district, landmark, urban, historical site, government agencies, major tourist areas, and etc. This is to develop and improve way of learning and historical tourism for ancient architecture and its surroundings.